Bahasa Inggris Bahasa Inggris - Vika Ma'rifatun Nisa; Pradipta Kurniasanti; Fatimah Azzahra Mutmainah (Media Gizi Kesmas, 2025)
Background: Nutritional problems among junior high school adolescents in Indonesia remain high due to a lack of knowledge about balanced nutrition, which is caused by suboptimal counseling due to the use of less interactive methods. Modifications to more interactive methods, such as pop-up demonstrations and card games, are needed. Objectives: To determine the difference in effectiveness between the pop-up demonstration and card game methods in improving students knowledge about balanced nutrition at SMP Negeri 44 Semarang. Methods: A quantitative method with a true-experimental design of two-group pretest-posttest without control and a proportional stratified random sampling technique. The sample consisted of 64 ninth-grade students, with each group consisting of 32 students. Data analysis used the Wilcoxon test to determine the difference in knowledge before and after the counseling of each method, as well as the Mann-Whitney test to determine the difference in effectiveness of the two methods. The instruments needed for this study are a balanced nutrition tumpeng pop-up, game cards, and a 30-question pretest-posttest questionnaire. Results: Before the pop-up demonstration method, only 5 (15.6%) of the sample were in the good category, which increased to 20 (62.5%) after the pop-up demonstration method. There was a difference in student knowledge before and after the pop-up demonstration method (p<0.001). Before the card game method, only 7 (21.9%) of the sample were in the good category, which increased to 20 (62.5%) after the card game method. There was a difference in student knowledge before and after the card game method (p<0.001). There was no difference in effectiveness between the pop-up demonstration and card game methods (significance 0.478>0.05). Based on the mean rank, the pop-up demonstration method was more effective. Conclusion: The pop-up demonstration method and the card game were equally effective in increasing student knowledge.